The impact of systemic sclerosis on oral health - Alina Stanomir; Iulia Cristina Micu; Andrada Soancă; Andreea Ciurea; Cristina Pamfil; Simona Rednic; Alexandra Roman (Amaltea Medical Publishing House, 2022)
Systemic sclerosis (SSc) is a rare connective tissue disorder characterized by a wide range of manifestations, including oral changes. The pathogenesis of SSc is complex and remains incompletely understood. In the development of SSc following mechanisms are involved: immune activation, vascular alterations, and increased accumulation of extracellular collagen matrix. Genetics plays an important role in SSc development. Oral manifestations of SSc include microstomia, xerostomia, telangiectasia, periodontitis, increased width of the periodontal ligament, and alveolar bone resorption. These manifestations are a significant cause of comorbidities and a decreased quality of life in SSc patients. Education on oral hygiene and home-based orofacial physiotherapy may improve the oral status of these patients. A multidisciplinary team should be involved in the management of SSc.